SH3BGRL3 binds myosin 1c and is involved in MDA-MB-231 cell migration - Di Pisa, Filippo; Pesenti, Elisa; Bono, Maria; Tenca, Claudya; Scaloni, Andrea; Bruno, Silvia; Fais, Franco; Scartezzini, Paolo; Ghiotto, Fabio (Italian Journal of Anatomy and Embryology, 2017)
SH3BGRL3 is a gene belonging to SH3BGR family, it is ubiquitously expressed and encodes for a 93 AA thiorerodoxin-like protein evolutionarily conserved. A proteomic study reported that SH3BGRL3 binds the cytoplasmatic domain of ERBB2 receptor. On this basis we performed immuno-staining experiments in FLAG-SH3BGRL3 transfected SKBR3 cell line that showed SH3BGRL3 and ERBB2 co-localization. Nonetheless, co-immunoprecipitation (Co-IP) of ERBB2 using FLAG-SH3BGRL3 as bait and vice versa was not achievable. Therefore, to investigate SH3BGRL3 potential interactors we performed Co-IP experiments from SKBR3 lysates transfected with FLAG-SH3BGRL3 followed by mass spectrometry analysis. The results revealed myosin 1c (Myo1c) as a candidate interactor. Subsequent Co-IP experiments followed by WB analysis validated the interaction between the two proteins. To map the interaction site we performed Co-IP experiments using SKBR3 cells co-transfected with FLAG-SH3BGRL3 and HA tagged deletion mutants of Myo1c that showed SH3BGRL3 binding to the neck region of Myo1c. Since Myo1c neck region binds calmodulin in a Ca2+ dependent way, we assessed if the binding was Ca2+ dependent also for SH3BGRL3. The experiments showed that SH3BGRL3 binds the Myo1c neck in presence of Ca2+, differently from calmodulin that binds it in absence of Ca2+. Myo1c is a motor protein involved, among its different functions, in cell membrane dynamics. Thus we investigated SH3BGRL3 involvement in cell migration using MDA-MB-231 cell line. We transfected MDA-MB-231 cells with FLAG-SH3BGRL3 and performed immuno-staining and Co-IP experiments that showed co-localization and interaction of Myo1c and SH3BGRL3. Accordingly, we performed migration assays using boyden chambers after silencing or not SH3BGRL3 expression by means siRNAs. The results showed a statistically significant decrease in migration capacity of silenced cells respect to controls. Our data show that SH3BGRL3 binds Myo1c neck region in a Ca2+ dependent way and that this interaction is involved in cell migration in our model.